2020
DOI: 10.31616/asj.2019.0004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Bone Loss with Bone Turnover Markers Following Acute Spinal Cord Injury

Abstract: To evaluate bone turnover markers (BTMs) in individuals with acute spinal cord injury (SCI) and to compare the results with those of healthy controls and postmenopausal females. Overview of Literature: SCI significantly impacts bone health. Change in bone mineral density appears 6 months after SCI and rapid bone loss during the acute phase is often underestimated, resulting in osteoporosis and a high risk of sublesional fractures. However, few studies have evaluated BTMs in the Indian SCI population. Despite a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…In patients with LSS, a decrease in the therapeutic effect of ibandronate may also be associated with deterioration of bone metabolism [ 24 ]. Lee et al [ 14 ] reported that 55.6 % of patients with LSS had hypovitaminosis D, which reduced the effectiveness of osteoporosis treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with LSS, a decrease in the therapeutic effect of ibandronate may also be associated with deterioration of bone metabolism [ 24 ]. Lee et al [ 14 ] reported that 55.6 % of patients with LSS had hypovitaminosis D, which reduced the effectiveness of osteoporosis treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with LSS, a decrease in the therapeutic effect of ibandronate may also be associated with deterioration of bone metabolism [24]. Lee et al [14] reported that 55.6% of patients with LSS had hypovitaminosis D, which reduced the effectiveness of osteoporosis treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Ankylosing spondylitis [99], RA [100], SLE [101] Neurological and musculoskeletal risk factors Epilepsy [102,103], Multiple sclerosis [104], Muscular dystrophy [105], Parkinson's disease [106], Spinal cord injury [107,108], Stroke [109] Miscellaneous conditions and diseases Addiction to narcotics [110], AIDS/HIV [111,112], Amyloidosis [113], Chronic metabolic acidosis, COPD [114], CHF [115], Endstage renal disease [116], Hypercalciuria [117], Idiopathic scoliosis [118], post-transplant bone disease [119], Socioeconomic status [120], Sarcoidosis [121], Weight loss [122] Long-term calcium intake is essential in building bone reserves before the PBM level and maintaining bone mass later at age twenty. The risk of secondary OP can be initiated by calcium deficiency [123] or lack of absorption [124].…”
Section: Rheumatologic and Autoimmune Diseasesmentioning
confidence: 99%